Determining noise levels in the electric power plant in Baniyas refinery and mapping the noise using GIS - نعمان, سومر; بدر الدين عابدين , (Latakia University Journal -Engineering Sciences Series, 2023)
Industrial noise is one of the pollutants that greatly affect the health of workers, and exposure to noise doses in excess of the permissible values ​​causes the worker to feel uncomfortable, and it is difficult for workers to communicate with each other, in addition to anxiety and tension, and with the passage of time and repeated exposure, problems affecting health appear. Such as high blood pressure, ischemia and partial or total hearing loss. Proceeding from the importance of the subject, this research was carried out at the electric power plant in Baniyas refinery, to find out the level of noise that the worker is exposed to in the operating room, during the normal course of work in it, and to conduct a comprehensive survey of the level of noise, which was measured at 25 points spread in the hall The noise map was drawn using a geographic information system (GIS), In order to determine the dangerous and safe places according to the measurement and prediction data based on one of the interpolation methods used by this system, where the result was 84.1 dB, which is the lowest value recorded, and 110.1 dB as the highest value, according to Map There are large areas in the hall above the locally and internationally set level for the shift work (8 hours), which is 85 decibels.